A novel risk model of cholesterol metabolism-related mRNAs for predicting overall survival and immune signature in glioma based on machine learning and multi-omics data - Yu, Danlei; Shen, Kecheng; Wang, Jun; Jiang, Fan; Xia, Pengfei; Yu, Zhengquan (Translational Cancer Research, 2026)
The intricate molecular pathways involved in gliomas, coupled with the shift toward more personalized treatment approaches, necessitate the identification of novel and dependable molecular targets. Cholesterol metabolism is a key player in modulating metabolic alterations in glioma cells and shaping the tumor immune microenvironment. Consequently, thoroughly examining messenger RNAs (mRNAs) within this pathway has emerged as a novel avenue for investigating the prognostic markers and immunotherapeutic targets for glioma, which also constitutes the objective of the present study.